2014
DOI: 10.3846/13926292.2014.960016
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Solitary Waves and Periodic Waves to a Perturbed Generalized KDV Equation

Abstract: In this paper, the existence of solitary waves and periodic waves to a perturbed generalized KdV equation is established by applying the geometric singular perturbation theory and the regular perturbation analysis for a Hamiltonian system. Moreover, upper and lower bounds of the limit wave speed are obtained. Some previous results are extended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…After the works of Derks and Gils [9] and Ogawa [36], in 2014 Yan et al [47] investigated the perturbed generalized KdV equation,…”
Section: Xianbo Sun and Pei Yumentioning
confidence: 99%
See 2 more Smart Citations
“…After the works of Derks and Gils [9] and Ogawa [36], in 2014 Yan et al [47] investigated the perturbed generalized KdV equation,…”
Section: Xianbo Sun and Pei Yumentioning
confidence: 99%
“…Yan et al [47] proved that there exists one periodic wave by choosing some wave speed c for sufficiently small > 0. However, the uniqueness of the periodic wave is still open.…”
Section: Xianbo Sun and Pei Yumentioning
confidence: 99%
See 1 more Smart Citation
“…The traveling wave solutions, especially the solitary wave solutions of these equations have attracted extensive attentions and some effective techniques or methods have been proposed, among which the dynamical system method [10][11][12][13][14] are well applied to investigate the traveling wave solutions of various nonlinear wave equations. In particularly, it has been shown that equation (4) (or(5)) with n > 1 admits a kind of solitary waves with compact support and therefore are named as compactons [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the perturbed KdV equation ( 6) is a special case l = 1 and m = 2 of equation ( 7), so it is a generalization of the perturbed KdV equation. Guo and Zhao [17] have examined the existence of periodic waves for equation (7) with l = 3 and m = 5; The particular case that (7) with l = 1 and arbitrary m ∈ Z + , also named as singularly perturbed higher-order KdV equation, has been investigated in [12,18] via geometric singular perturbation theory.…”
Section: Introductionmentioning
confidence: 99%